The Role of Urban Place in Activating Urban Competition in Baghdad City as a Case Study (Journal of Engineering, 2025)
This study examines the concept of urban competition, focusing on the role of heritage urban places in enhancing urban competitiveness. Urban competition refers to a city's ability to possess economic, social, cultural, and security-related competitive advantages within its geographical region compared to other competing cities. Public places and urban landscapes—particularly heritage ones—attract tourists and institutions, thereby enhancing the city's image and interactively influencing the quality of urban life. A relatively rich cultural heritage and urban atmosphere in modern cities contribute to improving the quality of the place or attracting various stakeholders (such as institutions and professionals). Many cities around the world boast a rich cultural diversity that contributes to their overall attractiveness, which in turn reflects on their regional status and global standing, thereby influencing urban competition. Definitions of urban space, heritage, urban competition, and the factors that activate it were reviewed, along with a discussion of previous studies to identify the research problem, which is the "knowledge gap in studying the role of heritage urban places in activating urban competition." The research objective was identified as "activating urban competition through heritage urban places." To determine the relationship between urban places with cultural heritage value and their impact on urban competition, a theoretical framework was developed that includes the dependent variable (urban competition) and its indicators in urban places. This framework was then applied to two case studies in the city of Baghdad. Results were presented and analyzed, leading to conclusions that emphasized the importance of cultural heritage, quality of place, and quality of life in urban places in activating urban competition.